2013
DOI: 10.1021/ja310064v
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Mechanistic Studies of an Antiamyloidogenic Self-Assembled Cyclic d,l-α-Peptide Architecture

Abstract: Misfolding of the Aβ protein and its subsequent aggregation into toxic oligomers are related to Alzheimer's disease. Although peptides of various sequences can self-assemble into amyloid structures, these structures share common three-dimensional features that may promote their cross-reaction. Given the significant similarities between amyloids and the architecture of self-assembled cyclic D,L-α-peptide, we hypothesized that the latter may bind and stabilize a nontoxic form of Aβ, thereby preventing its aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
129
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 65 publications
11
129
0
1
Order By: Relevance
“…In addition, the dot-blot immunoassay confirmed that the inhibitory effect of CP-2 was stronger toward the more toxic Aβ42. These findings collectively suggested that CP-2 interacted and altered the aggregation of Aβ to an "off-pathway" mechanism [38,58].…”
Section: Conformational Mimicsmentioning
confidence: 78%
See 4 more Smart Citations
“…In addition, the dot-blot immunoassay confirmed that the inhibitory effect of CP-2 was stronger toward the more toxic Aβ42. These findings collectively suggested that CP-2 interacted and altered the aggregation of Aβ to an "off-pathway" mechanism [38,58].…”
Section: Conformational Mimicsmentioning
confidence: 78%
“…Reports have previously emphasized the importance of intermolecular hydrogen bonds and the cyclic nature of the macrocyclic subunit for self-assembly as well as antiviral and antibacterial activity of cyclic peptides [56,63]. The combined results of ThT, critical micelle concentration, and NMR analyses of CP-2 confirmed that self-assembly was essential for anti-amyloidogenic activity and that the bioactive form of CP-2 was probably selfassembled [58].…”
Section: Conformational Mimicsmentioning
confidence: 82%
See 3 more Smart Citations